Technology in the emergency department: Using cognitive work analysis to model and design sustainable systems. (March 2022) - Austin, Elizabeth E.; Blakely, Brette; Salmon, Paul; Braithwaite, Jeffrey; Clay-Williams, Robyn
Highlights: Application of the CWA Framework identified constraints on the design and integration of new technologies in the ED arising from the concentration of functions and agents in critical spaces. To improve ED work, the redistribution of non-clinical workload from human agents to non-human agents through technological interventions would redirect critical clinical expertise back to clinical tasks. A 'dynamic sustainability' approach between the ED system context and operational constraints of technology is critical for the provision of safe, high quality care. The CWA framework highlights factors within the delivery context that need to be considered when designing technology that is fit-for-purpose in the dynamic ED context. The models identify unintended system vulnerabilities introduced by current technology interactions, providing clear guidance for the design of future technological innovations intended to improve ED safety and performance. Abstract: Emergency Departments (EDs) are highly complex healthcare settings that must be resilient to unpredictable demands. New technologies are regularly introduced into EDs to improve patient care and workflow processes. However, the interaction between social and technical agents can introduce further complexity, making it difficult to identify the factors that influence the dynamic sustainability of interventions. This study aimed to demonstrate how the Cognitive Work Analysis (CWA) Framework can be used to model and design sustainable social-technical ED systems. To identify workspaces, social, technical, and collaboration factors that can be used to design and implement contextually appropriate technologies into the ED, we applied Control Task Analysis (i.e., Contextual Activities Template, CAT), Social Organizational and Cooperation Analysis (SOCA), and Strategies Analysis (StrA) phases from the CWA Framework, developed and validated using data collected during 263 h of observation in a large metropolitan ED. Our models revealed workspaces within the ED that are heavily involved in both clinical and non-clinical tasks for nurses and doctors using a range of technology. Workspaces, technology, and roles that are over- or under- utilized create contextually sensitive opportunities for dispersing work. Application of CWA enables examination of the ongoing, dynamic relationship between technological interventions and context, which can support sustainability and inform future designs.